Efficacy of polyhexamethylene biguanide nanoparticles to control mastitis causing Staphylococcus aureus - Leite, Renata de Freitas (2023)
Staphylococcus aureus is a bacteria associated with chronic mastitis due to virulent properties that enables to colonize cow´s mammary gland and to evade immune system and antimicrobial therapy. Polyhexamethylene biguanide (PHMB) is a polymer that presents a broad spectrum of antimicrobial activity, even against mastitis causing pathogens. Considering that nanotechnology is an innovative strategy against infectious diseases once it enhances the antimicrobial activity of the active compounds and usually presents low toxicity, the overall objective of this study was to test the efficacy of a nanoformulation composed of polyhexamethylene biguanide (PHMB NPs) against mastitis causing Staph. aureus. The present thesis was structured in two studies. In the Study 1, we evaluated the antimicrobial activity of PHMB NPs and PHMB against 20 isolates of milk origin Staph. aureus by microdilution assay to determine their minimum inhibitory concentrations (MIC) compared with chlorhexidine gluconate (CHG), povidone-iodine (PVP-I), and sodium dichloroisocyanurate (NaDCC). PHMB-NPs inhibited 90% of tested isolates at the lowest MIC value (<0.03 µg/mL), followed by CHG (≥0.25 µg/mL), PHMB (≥0.5 µg/mL), NaDCC (≥500 µg/mL) and PVP-I (≥8,000 µg/mL). In Study 2, we selected and evaluated 10 Staph. aureus isolates, which were resistant to antimicrobials used for mastitis treatment, and presented the ability to invade bovine mammary epithelial cells (MAC-T cells) and to form biofilm. Study 2 was further divided into 2 experiments. Experiment 1 focused on the possibility of PHMB NPs and PHMB use for intramammary treatment aiming to combat biofilm formation. First, we verified that MAC-T cells did not have their viability altered till 4 µg/mL of PHMB NPs and PHMB. Then, we investigated the anti-biofilm activities of PHMB NPs and PHMB by crystal violet and colony count assays. PHMB NPs and PHMB presented a high efficacy in preventing biofilm formation at concentrations ≥0.12 µg/mL and ≥4 µg/mL, respectively. However, PHMB NPs and PHMB presented a limited efficacy against preformed biofilms. Experiment 2 focused on the use of PHMB NPs and PHMB as a teat disinfectant using the excised teat model (CHG, PVP-I, and NaDCC were used as control). PHMP NPs did not significantly reduce recovered Staph. aureus from teats (mean reduction of 37.57%) comparing to undipped control and to the other disinfectants, which may be related to a short contact. Finally, our results suggest that PHMB NPs and PHMB present a high potential to inhibit Staph. aureus growth and biofilm formation.